Implementation of Quality Management Tools to Improve Customer Service at “Heladería Copitos” - Gutierrez Melendez, Diego Ronaldo; Colque Colque, Karla Luana; Quispe Vásquez, Luis Roberto (LACCEI, 2025)
This study focuses on improving customer service at the artisanal ice cream shop “Copitos” in Cajamarca by applying quality management tools such as the PDCA cycle, House of Quality, FMEA, and the 8D methodology. Initially, deficiencies in staff friendliness and service speed were identified using SERVQUAL surveys, showing a general satisfaction level of 70%. Corrective actions aligned with customer expectations were designed and implemented, prioritizing staff training and the optimization of critical processes. After applying these tools, customer satisfaction increased to 96%, reflecting significant improvements in speed, service friendliness, and product presentation. The results demonstrate that quality management is not limited to large organizations but can be successfully implemented in small artisanal businesses, enabling them to strengthen customer loyalty and establish a culture of continuous improvement. This work highlights that acting upon collected data is essential for achieving sustainable results, generating positive impacts on customer experience and the company’s competitiveness.